ANALISIS KINERJA BELANJA DALAM LAPORAN REALISASI ANGGARAN (LRA) PADA KEMENTERIAN KESEHATAN REPUBLIK INDONESIA TAHUN ANGGARAN 2019-2021 - Amelia, Panca Safira; Nursyahbani, Daniswara; Bharata, Risma Wira (Politeknik Negeri Ambon, 2023)
The information in the Budget Realization Report (LRA) that has been published by a public institution can be used to improve the situation’s financial performance. The Budget Realization Report is one of several work unit financial accountability reports that are still in use. Report readers will be able to conduct an analysis of the performance of financial reports, including an analysis of income, an analysis of expenditure, and an analysis of financing, according to Budget Realization Report. The purpose of this research is to find out and analyze the spending performance in Budget Realization Report of the Ministry of Health Republic Indonesia. the analysis method used in this study is the descriptive quantitative method. The following analysis wa carried out: Analyzes of the Variants of Expenditure (Spending Difference), Expenditure Growth, Conformity of Expenditure, and Efficiency of Expenditure. Based on the analysis that was done, it can be seen that the Budget Realization Report of The Ministry if the Health for the 2019, 2020, and 2021 will be as: Variances are higher in 2019 (5,40%) than 2020 (4,50%) and 2021 (2,85%), meanwhile spending growth ratio at the start of Coronavirus Pandemic, 2020, increased by 51,90%. At 2021 spending growth faster that is 103,81%. After the Pandemic Covid-19, the Ministry of Health reported an increases of 77,85% as a result of the overall expenditure growth